Pre-existence, wisdom, and the Son of Man: a study of the idea of pre-existence in the New Testament - Hamerton-Kelly, Robert (Society for New Testament Studies monograph series, 1973)
The idea of pre-existence has a long history in early Jewish and Biblical traditions. Professor Hamerton-Kelly studies the various forms the idea takes in these traditions as they emerge in the New Testament. He pays special attention to the themes of Wisdom and the Son of Man, with detailed references to the relevant texts and sources. His conclusions are that there are two basic types of the idea of pre-existence in the New Testament - which he calls 'protological' and 'eschatological' respectively - and two entities which were chiefly understood in terms of these types - namely, Christ and the Church. This unusual book illuminates the process by which the early Church blended its Greek and Jewish heritages by analysing some of the conceptual patterns in the New Testament which anticipated that process. It will be of interest to New Testament scholars and historians of doctrine.